A Comprehensive Review of Systemic Sclerosis: Diagnosis, Clinical Features and Management Strategies - Borowiec, Agnieszka; Borowiec, Kinga; Kwaśniewska, Paulina; Biernikiewicz, Julia; Biernikiewicz, Milena; Wilewska, Anna; Pomirski, Bartosz; Pomirska, Agata; Alabrudziński, Konstanty; Kałachurska, Miszela (Journal of Education, Health and Sport, 2025)
Introduction Systemic sclerosis (SSc) is a rare autoimmune disease characterized by fibrosis of the skin and internal organs, along with vasculopathy. It is associated with significant morbidity and mortality, particularly due to pulmonary and renal complications. Early diagnosis is challenging, but crucial, as severe internal organ involvement can occur within three years of disease onset. SSc is categorized into subsets, such as diffuse and limited cutaneous forms with varying degrees of skin and organ involvement. Specific autoantibodies are critical for diagnosing and predicting disease severity and understanding these serological profiles aids in personalized treatment decisions. Management focuses on addressing specific manifestations like Raynaud’s phenomenon, skin fibrosis, pulmonary involvement, and gastrointestinal issues with treatment strategies tailored to the disease’s stage and organ involvement. Despite advances in treatment, SSc remains a challenging disease requiring ongoing vigilance for early detection and intervention. Purpose The purpose of this article is to provide a comprehensive overview of systemic sclerosis, focusing on its diagnostic criteria, clinical features and management strategies. It aimsto highlight the importance of early detection, particularly in the context of skin and organ involvement and the role of serological markers in guiding diagnosis and treatment. Ultimately, the goal is to improve awareness and understanding of SSc among healthcare professionals, particularly dermatologists, to enhance early diagnosis and optimize patient outcomes. Materials and Methods Our review is based on an analysis of material collected in 'Pubmed', 'Google Scholar' and other scientific articles using the keywords: systemic sclerosis, antinuclear antibodies, Raynaud’s phenomenon, pulmonary arterial hypertension.